High-field MRI findings in epileptic dogs with a normal inter-ictal neurological examination - Phillipps, Stephanie; Goncalves, Rita (Frontiers in Veterinary Science, 2025)
IntroductionEpilepsy is one of the most common chronic neurological conditions affecting dogs. Previous research exploring the likelihood of a structural cause of epilepsy specifically in dogs with a normal inter-ictal examination is limited to a small population of dogs using low-field MRI. The aims of this study were to establish high-field (1.0T and 1.5T) MRI findings in dogs presenting with epileptic seizures and a normal inter-ictal examination.MethodsMedical records were retrospectively searched for dogs presenting with at least two epileptic seizure events more than 24 h apart. To be included in the study, patients had to have a normal neurological examination, high-field MRI of the brain and have had metabolic and toxic causes excluded.ResultsFour hundred and twelve dogs were eligible for inclusion. Crossbreeds were most commonly affected (n = 63, 15.3%) followed by Border collies (n = 39, 9.5%) and Labrador retrievers (n = 26, 6.3%). Seventy-six dogs (18.5%) had abnormalities detected on MRI, 60 (78.9%) of which were considered to be incidental. Overall, 16 dogs (3.9%) had a structural cause of their epileptic seizures including neoplasia (n = 13, 81.3%), anomalous (n = 2, 12.5%) and meningoencephalitis of unknown origin (MUO) (n = 1, 6.3%). When split into age group at first epileptic seizure structural lesions were documented in 0/66 dogs aged <1 year, 4/256 (1.6%) dogs aged ≥1 year ≤6 years (three neoplastic and one anomalous), 3/51 (5.9%) aged >6 years ≤8 years (two neoplastic and one MUO), and 9/39 (23.1%) dogs aged >8 years (eight neoplastic, one anomalous). Multivariate analysis identified two risk factors for structural disease: increasing age at first epileptic seizure (p < 0.001, OR = 4.390, CI 2.338–8.072) and a history of status epilepticus (p = 0.049, OR = 4.389, CI 1.010–19.078).DiscussionStructural lesions are an uncommon cause of epilepsy at any age in dogs with a normal inter-ictal examination.